IDENTIFIKASI PENGARUH KEPADATAN BANGUNAN TERHADAP URBAN HEAT ISLAND DI PULAU BATAM MENGGUNAKAN CITRA LANDSAT 8 - Anurogo, Wenang; Sujiantoro, Erick Ikbal (Universitas Nusa Cendana, 2025)
The rapid population growth in Batam City has led to the conversion of green land into a built area to meet residential, industrial, and infrastructure needs. This change in land use has an impact on increasing surface temperature and triggers the Urban Heat Island (UHI) phenomenon. UHI is characterized by higher temperatures in urban areas compared to surrounding areas due to changes in land cover. This study aims to identify land surface temperature, UHI phenomenon, building density level (NDBI), and the influence of NDBI on UHI on Batam island. The results showed significant variations in land surface temperatures across the island, with a range between 18°C to 33°C. This temperature difference directly contributes to the formation of the UHI phenomenon on Batam Island. The NDBI map of Batam Island shows that the UHI phenomenon tends to be concentrated in areas with high building densities such as in urban center, industrial and residential areas. The regression results between NDBI and UHI showed the influence of NDBI on UHI by 71%, which shows that the relationship between the UHI and NDBI variables has a positive and proportional relationship. The results also show that the higher the density of the building, the intensity of the UHI will also increase. This study confirms that the increase in building density is the factor that encourages the occurrence of the UHI phenomenon in Batam Island.